Psychologically-Based Voting with Uncertainty - Arianna Degan; Ming Li (Center for Economic Studies and ifo Institute (CESifo), 2014)
We analyze a psychologically-based model of voter turnout in an election with common value and uncertainty. Our model yields distinctive comparative statics results. First, an increase in the proportion of informed citizens may cause the winning margin for the right candidate to either rise or fall. In addition such increase can have a non-monotonic effect on turnout of uninformed citizens. Second, as the prior becomes more favourable towards the ex ante favoured candidate, turnouts of informed and uninformed voters both change in a non-monotonic way. Furthermore, total turnout can be positively or negatively correlated with winning margins.
Keywords: D72; 330; regret; voter turnout; behavioural political economy; psychology and economics; uninformed voters; informed voters